Rethinking Authorship: The Intersection of Artificial Intelligence and Intellectual Property Law in Uganda - Joel Atuhaire (Uganda Christian University, 2025)
Artificial Intelligence is no longer a distant concept; it is actively reshaping how we create, communicate, and express ideas. As machines begin to generate music, art, literature, and code, the question at the heart of this dissertation is both simple and complex: Who is the author when the creator is not human? This study critically examines how Uganda’s intellectual property law responds to the evolving reality of AI-generated content and whether our current legal frameworks are prepared for this shift. Drawing on Uganda’s Copyright and Neighbouring Rights Act, regional instruments, and international treaties like the Berne Convention, the research reveals a persistent reliance on human agency and intentionality, principles that are increasingly strained in an era of machine creativity. Through a comparative and doctrinal approach, the dissertation explores emerging legal models such as hybrid authorship, sui generis protections, and developer attribution, assessing their relevance and adaptability within Uganda’s unique socio-legal context. The argument is not for abandoning tradition but for reimagining it. If Uganda is to meaningfully participate in the digital and creative economies of the future, it must rethink how it defines and protects authorship. This work, therefore, offers a grounded yet forward-looking contribution to ongoing conversations about intellectual property, technological change, and legal reform not only in Uganda but across the Globe. It invites scholars, lawmakers, and creators to consider a legal future that is both imaginative and inclusive
This dissertation critically examines the evolving intersection between artificial intelligence (AI) and intellectual property (IP) law, with a particular focus on the concept of authorship in the Ugandan legal context. Rooted in doctrinal legal research, the study interrogates the extent to which Uganda’s Copyright and Neighbouring Rights Act, CAP 222, and related international instruments adequately respond to the challenges posed by AI-generated content. It explores whether the human-centric model of authorship—anchored in traditional legal theories such as labour, personality, and utilitarianism—can remain coherent and functional in an age where machines increasingly participate in, and sometimes independently generate, creative works. The study draws from comparative jurisdictions such as the United Kingdom, the United States, and Japan to highlight emerging legislative and judicial approaches to AI authorship. These insights inform a critical evaluation of Uganda’s legal preparedness and policy gaps in regulating AI-generated works. Ultimately, the dissertation argues for a reconceptualization of authorship and offers practical, legally grounded recommendations for reforming IP law in Uganda, ensuring it remains responsive, inclusive, and future-oriented in the face of rapid technological advancement.